Propensities of Amino Acid Pairings in Secondary Structure of Globular Proteins (vol 25, pg 328, 2020) - (:unkn) unknown (SPRINGER, 2020)
In the original version of this article, under the Introduction section in paragraph starting Some findings of this study... the Sect. 10 should be changed to Sect. 3.